Analisis Faktor-Faktor Kesulitan Belajar Materi IPA Semester I Kelas V Sekolah Dasar - Miftahul Khasanah; Diana Endah Handayani; Filia Prima Artharina (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This study aims to find out the difficulty of learning on ipa material, knowing the factors that cause IPA material learning difficulties. This type of research is qualitative with descriptive methods using interview techniques, questionnaires and documentation. Based on the findings found there are six students who have difficulty learning IPA. Internal factors that affect IPA learning difficulties are due to lack of health, body defects, low intelligence, low student interest in learning and less learning motivation. External factors that affect IPA learning difficulties are the way parents educate children less optimally, the lack of parental attention to student learning activities, parents and children's relationships are not good, the atmosphere of the house that interferes with student concentration while studying, the undisciplined learning, and the influence of mass media and associates who are less supportive of learning culture. Based on the results of research advice that can be delivered, the teacher must provide motivation that can increase learning interest and teachers must be able to detect learning problems that occur in their class. Parents are expected to pay attention to the development of their children's learning both in school and at home.